Long-term influenza antibodies profiles in previously vaccinated and non-vaccinated adults - Iván Sanz-Muñoz; Conrado Lajara; Javier Sánchez-Martínez; Camino Prada-García; Silvia Rojo-Rello; Marta Domínguez-Gil; Virginia Fernández-Espinilla; Cristina Hernán-García; José M. Eiros-Bachiller; Asunción Caminero-Pérez; Yolanda Marcos-López; Luis Teso-Fernández; et al. (Taylor & Francis Group, 2023)
The aim of this work is to describe the dynamics of influenza antibodies after vaccination in adults. We conducted a case-cohort serological study in the automobile manufacturing plants of the Renault España S.A. group in Valladolid and Palencia (Spain), including 550 workers (66.9%) previously vaccinated against influenza (group V), and 272 (33.1%) never vaccinated (group NV). A pre-vaccination serum sample was collected, another after 30-40 days and another after 6 months. The dynamics of antibodies were analyzed. A lower seroprotection of NV before vaccination was observed, but an antibody response between 2 and 4 times higher than in V was assessed. After 6 months, antibodies declined in both groups until equalize. Antibodies titers decrease with age, and no differences were found among underlying pathologies. Adults never vaccinated against influenza had lower seroprotection than those previously vaccinated, but influenza vaccination produces a more intense serological response in them, acquiring significantly higher antibody titers than those previously vaccinated. The antibodies, although in lower titers, persist and equalize among both groups at least 6 months after vaccination, which allows the individual to be protected during the entire circulation of the influenza virus in the same season.